Psalm 22 LXX in Origen’s commentary on the Song of Songs - P.B. Decock (Acta Theologica)
This article examines three distinct ways of reading Psalm 23(LXX 22), first in the Targum, then in the liturgy of early Christian initiation, and finally in Origen’s commentary on the Song of Songs. The Targum focuses on God’s protective presence in Israel’s history and looks forward to the salvation to come. Reading the psalm in the context of Christian initiation draws out the contextual possibilities of the text. In his interpretation of the Song of Songs, Origen seeks elements of spiritual progress after the stage of initiation. The “inebriating cup” points to a strongly affective dimension of this process.